Expanding the VEXAS diagnostic workup: the role of peripheral blood cytological analysis - Baggio, Chiara; Oliviero, Francesca; Padoan, Roberto; Iorio, Luca; Bixio, Riccardo; Orsolini, Giovanni; Bertoldo, Eugenia; Bernardi, Cristina; Colavito, Davide; Paiero, Barbara; Pregnolato, Giovanna; Ramonda, Roberta; et al. (Frontiers in Immunology, 2024)
VEXAS syndrome is a newly described autoinflammatory entity characterized by somatic mutations in the UBA1 X-linked gene in hematopoietic progenitor cells. Several studies have demonstrated that the presence of vacuoles in progenitor cells from bone marrow aspirates is a hallmark finding for this syndrome. Therefore, this study aimed to characterize leukocytes from VEXAS patients versus patients with ANCA-associated vasculitis (AAV), familial Mediterranean fever (FMF), and healthy donors (HD) to define a specific cytological pattern that can support VEXAS diagnosis. Twelve VEXAS patients were included in the study. FMF (n = 16), AAV (n = 16) and HDs (n = 20) acted as controls. May-Grünwald Giemsa staining was used for studying cellular morphology, including cytoplasm, granules, and vacuoles and to perform a cytogenic evaluation of leucocytes. Plasma IL-1β, IL-1α, TNFα, IL-18 and IL-8 were measured using ELISA assay. The cytological analysis from blood smears confirmed the presence of immature neutrophils in VEXAS patients. We found a greater number of vacuoles in VEXAS patients vs. FMF, AAV and HD. Micronuclei (MNi) and cell death rate were higher in VEXAS patients vs. HD. Cell death correlated with IL-1β and IL-8 levels. MNi were positively associated with IL-8 and IL-1β levels, and with the percentage of immature neutrophils and vacuoles. In conclusion, our findings suggested that cytological test may be supportive for VEXAS diagnosis, despite genetical analysis is mandatory for confirming the disease. We identified several cytological hallmarks that may distinguish the VEXAS "cytotype" not only from HD but also from other inflammatory diseases.